2019
DOI: 10.1016/j.jcrs.2019.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of trifocal intraocular lenses on standard autorefraction and aberrometer-based autorefraction

Abstract: To study the agreement between manifest refraction and objective refraction measured with two autorefractor models and an aberrometer in eyes implanted with a trifocal diffractive intraocular lens (IOL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 29 publications
3
26
0
Order By: Relevance
“…However, autorefraction has been shown to provide only a nominally more minus refraction relative to subjective methods. 16 In conclusion, the current study demonstrates that both the non-toric and toric versions of the trifocal IOL evaluated here provide excellent functional vision to patients, with good distance, intermediate and near uncorrected VA, a wide range of vision and good contrast sensitivity. We believe this is the largest study of clinical outcomes for this particular trifocal lens that has been reported to date.…”
Section: Discussionsupporting
confidence: 53%
“…However, autorefraction has been shown to provide only a nominally more minus refraction relative to subjective methods. 16 In conclusion, the current study demonstrates that both the non-toric and toric versions of the trifocal IOL evaluated here provide excellent functional vision to patients, with good distance, intermediate and near uncorrected VA, a wide range of vision and good contrast sensitivity. We believe this is the largest study of clinical outcomes for this particular trifocal lens that has been reported to date.…”
Section: Discussionsupporting
confidence: 53%
“…It is interesting to note that similar to this study, Garzón et al found that overall AR values had a trend to slightly more negative values, specially for the SE (M). Besides the fact that Garzón et al 17 did not include astigmatic patients, it should be also mentioned that the spherical trifocal lens analyzed in their study has a different optical design and direct comparisons should be made with caution. At the same time, other authors have studied the validity of devices for analyzing ocular parameters (i.e.…”
Section: Discussionmentioning
confidence: 96%
“…Garzón et al 17 have recently analyzed the influence of a trifocal IOL on AR methods. It is interesting to note that similar to this study, Garzón et al found that overall AR values had a trend to slightly more negative values, specially for the SE (M).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations